2012
DOI: 10.1093/rpd/ncs188
|View full text |Cite
|
Sign up to set email alerts
|

Levels of thoron and progeny in high background radiation area of southeastern coast of Odisha, India

Abstract: Exposure to radon, (222)Rn, is assumed to be the most significant source of natural radiation to human beings in most cases. It is thought that radon and its progeny are major factors that cause cancer. The presence of thoron, (220)Rn, was often neglected because it was considered that the quantity of thoron in the environment is less than that of radon. However, recent studies have shown that a high thoron concentration was found in some regions and the exposure to (220)Rn and its progeny can equal or several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The thickness of the films was adjusted to absorb the energy of alpha particles from radon, thoron and their progenies except for 212 Po (8.78 MeV). Since the Raduet and thoron progeny deposition detector are inexpensive and easy to use, they are often used in a large-scale survey (e.g., Chen et al, 2012;Janik et al, 2013;Kudo et al, 2015;McLaughlin et al, 2011;Ramola et al, 2010Ramola et al, , 2012.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the films was adjusted to absorb the energy of alpha particles from radon, thoron and their progenies except for 212 Po (8.78 MeV). Since the Raduet and thoron progeny deposition detector are inexpensive and easy to use, they are often used in a large-scale survey (e.g., Chen et al, 2012;Janik et al, 2013;Kudo et al, 2015;McLaughlin et al, 2011;Ramola et al, 2010Ramola et al, , 2012.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…In this area, surveys on radon and thoron concentrations in dwellings were carried out and they revealed that thoron concentration is higher than radon concentration (e.g., Ramola et al, 2010Ramola et al, , 2012Sulekha Rao and Sengupta, 2010). Sulekha Rao and Sengupta (2010) also attempted to calculate the dose due to inhalation of thoron (including its progeny) based on measurements of thoron gas.…”
Section: Introductionmentioning
confidence: 99%
“…Although radiological importance of radon and its progeny has been acknowledged a long time ago, thoron had often been neglected due to its short half-life. The contribution of thoron to radiation doses has recently been recognized 6 7 8 9 . Many studies found that thoron can be a significant contributor to the radiation dose in residential buildings in some Asian, European and American countries 7 10 11 12 .…”
mentioning
confidence: 99%
“…This is known as emanation process and the total amount of radon emitted by pore space to environment is called the exhalation. The fraction of radon emanation and its exhalation rate depend on the geology of the area, soil porosity, structures (shears, faults and thrusts) and associated uranium mineralization (Choubey & Ramola, 1997;Duenas & Fernandez, 1987;Holkko & Liukkonen, 1993;Hubbard & Hagberg, 1996;Hubbard, Hagberg, & Enflo, 1992;Markkanen & Arvela, 1992;Prasad, Prasad, Gusain, Choubey, & Ramola, 2008;Ramola & Choubey, 2003;Ramola et al, 2012;Ramola, Singh, & Virk, 1988). Radon emanation rate is highest when soil moisture is between 15 and 20% in weight (Damkjaer & Korsbeck, 1985;Lindmark & Rosen, 1985;Stranden, Kolstad, & Lind, 1984).…”
Section: Introductionmentioning
confidence: 99%